KESALAHAN KALIMAT DALAM TEKS EKSPOSISI SISWA KELAS VII 7 SMP NEGERI 12 PADANG - Nurtia, Syafni; Manaf, Ngusman Abdul; Emidar, Emidar (Universitas Negeri Padang, 2016)
ABSTRACTÂ The research was conducted to describe the sentence errors in the exposition text in some aspects (1) the structure of syntactical function (2) the lack of sentence element (3) the surplus of sentence element (4) the diction (word selection), and (5) spelling (capital letters, writting word, and punctuation). It employed a descriptive qualitative method. The instrument of this study was the researcher herself. The data of this study was the wrong sentences of exposition text of the students at grade VII 7 of SMP Negeri 12 Padang. The data were collected by borrowing the students exposition text from the teacher and copying. The data were analyzed by (1) stoctaking the data (2) identifyng the sentence errors (3) analysing the sentence errors, and (4) concluding the result of this study. The result shows. First, the sentence errors on syntactical function is an inappropriate use of predikat. Second, the sentence errors on lack of sentence element are not available the subject, predikat, and conjunction. Third, the sentence errors on the surplus of sentence element are the overlapping use of plural and repetition of words. Fourth, the sentence errors on diction (word selection) are an inappropriate concept used and collocation. Fifth, the sentence errors on spelling are writing the capital letters, writing the basic words, writing the derivative words, writing the repetition of words, writing prefix di-, writing the abbreviation words, writing the foreign words, and the error use of punctuation suchlike full stop and comma.Â Kata kunci: kesalahan kalimat, teks eksposisi